USING OPEN SCIENCE SERVICES TO IMPROVE DISTANCE, COMBINED AND FAMILY FORMS OF LEARNING IN GENERAL EDUCATION INSTITUTIONS - Sukhikh, Alisa (Physical and Mathematical Education, 2023)
The article discusses an approach to learning that ensures the active participation of students in selecting educational materials and resources. Teachers can create conditions for students to choose learning materials individually, promoting their interest in learning. That will strengthen the personalized approach to learning, where each student can choose materials that meet their interests and needs. Formulation of the problem. The transition to distance blended and family learning became necessary due to the circumstances associated with the global COVID-19 pandemic and, later, martial law imposition in Ukraine. Under these conditions, open scientific resources have become integral to improving the learning process. Open science services will provide additional opportunities for education in an accessible and effective way, regardless of the location of participants in the implementation of training in various forms of education. Materials and methods. The article presents some results of the research carried out within the framework of the project "Cloud-based Open Science Systems in Teacher Education and Professional Development" (registration number 2020.02/0310) with the grant support of the National Research Foundation of Ukraine. Results. The prerequisites for the transition and the advantages and disadvantages of organizing distance, combined, and family learning are considered. Open science services are proposed to be used by teachers and students to study various disciplines, especially in the context of the limitations of the traditional form of education. Conclusions. The article discusses open science services and analyzes their importance for education. They can be a valuable tool for teachers and students in the context of restrictions related to the pandemic and political conflicts. The use of open scientific resources will increase the accessibility and effectiveness of education and allow the educational process to be adapted to modern requirements and challenges. Open science services position education as less limited by geographical location, as participants can acquire knowledge and skills in a remote form of learning. These open science services can also be helpful in organizing distance, blended, and family learning in general secondary education institutions. They promote the development of open science principles in the educational context and provide participants with new opportunities for learning and improvement..